A Novel Synthesis of Zinc Borates from a Zinc Oxide Precursor via Ultrasonic Irradiation - Ersan, Ali Can; Yildirim, Meral; Kipcak, Azmi Seyhun; Tugrul, Nurcan (SLOVENSKO KEMIJSKO DRUSTVO, 2016)
In this study, zinc borate hydrate (Zn3B6O12 center dot 3.5H(2)O) was synthesized from zinc oxide (ZnO) and boric acid (H3BO3) via a novel method of ultrasonic irradiation. X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR) and Raman spectroscopy were used to characterize the synthesized products. Scanning electron microscopy (SEM) was used to determine the effects of reaction time and reaction temperature on the morphology of the products. Thermal dehydration kinetics were studied using thermal gravimetry and differential thermal gravimetry analysis (TG/DTA). The Doyle and Kissinger non-isothermal kinetic methods were used to analyse the TG/DTA data. The XRD results confirmed the successful synthesis of Zn3B6O12 center dot 3.5H(2)O at a range of reaction temperatures and times. Additionally, FT-IR and Raman analysis of the products identified peaks specific to zinc borate. Using the methods of Doyle and Kissinger, the activation energies of thermal dehydration of zinc borate were found to be 341.61 kJ/mol and 390.17 kJ/mol, respectively.
Keywords: Zinc borate; ultrasonic irradiation; dehydration; thermal analysis; SONOCHEMICAL SYNTHESIS; PARTICLES; Chemistry